Making pictures of war : realia et imaginaria in the iconology of the ancient Near East - Battini, Laura, (Archaeopress ancient Near Eastern archaeology ;, 2016)
This work brings together the main discussions that took place at an international conference on the iconology of war in the ancient Near East, a subject never addressed at an international meeting before.